Analysis and influence of education and talent of managers on business communication in companies - ino Baricevic; Irijana Rajkovic (UTMS Journal of Economics, 2023)
The development of modern economies is based on the development of companies. Business communication in them is very interesting for research, especially which variables affect it. In order for a company to achieve a competitive advantage over other companies in the environment and achieve good internal business communication, it must have: an educated manager who has certain knowledge and skills, who knows and understands how to manage their talents and how to motivate their employees. Employee communication in companies is like a liquid that cannot be lived without. Communication determines the direction in which our personal and business life moves. Without communication, man hardly exists. In the modern digital world of the 21st century, the one who owns information is the monopolist of knowledge and management.
Keywords: I20; M10; 330; manager education; manager talents; business communication